PENGGUNAAN BIOMASA TITHONIA DAN PUPUK KANDANG SAPI DAPAT MENINGKATKAN PRODUKTIVITAS TANAMAN BAWANG PUTIH (ALLIUM SATIVUM L.) - PUTRA, ANAK AGUNG GEDE; GUNAMANTA, PANDE GEDE; WINTEN, KETUT TURAINI INDRA (Universitas Mahasaraswati Mataram, 2020)
This study aims to determine the use of Tithonia Biomass and Cow Manure which will increase the productivity of garlic plants. This research was conducted in the experimental garden of the Agrotechnology Study Program, Faculty of Science and Technology, Tabanan University. The research was carried out from October 2019 to December 2019, using a factorial randomized block design (RBD) design that was repeated three times. The treatments that were tried consisted of two factors, namely the Biomass Tithonia factor (0 t ha-1, 4 t ha-1, 8 t ha-1, 12 t ha-1) and the dosage factor of Cow Cage fertilizer (0 t ha-1, 10 t ha-1, 20 t ha-1, 30 t ha-1).The results of statistical analysis showed that the interaction between the osis of Tithonia biomass fertilizer and the dose of cow manure had a very significant effect (p <0.01) on the productivity parameters of garlic plants.Combinasidosis treatment of 8 t of Tithonia ha-1 biomass and 20 t of cow manure ha-1 showed the highest oven dry weight of ha-1 tubers was 1,320 t or higher 511.11% compared to the lowest oven dry weight of ha-1 tubers, which was shown by the combination treatment without Tithonia biomass fertilizer and cow manure, yes, ebesar 0.216 t